Sistem Multipartai di Era Pemerintahan Susilo Bambang Yudhoyono 2004-2009 - Siska Yuspita Sari (Dinamika Politik, 2012)
This is a study about multyparty system in Susilo Bambang Yudhoyono's regime on 2004 to 2009. The focus is about how the effect of multyparty system to presidential system in Indonesia in Susilo Bambang Yudhoyono's regime. The findings of this study, there are four important things to influence multi-party system to a presidential system in Indonesia. First, the multi-party system affect the fragile coalition in the House of Parliament bonding. Second, the excessive control of the House of Parliament compromise the effectiveness of government. Third, multi-party system affects the power of the vice president is more dominant in the government. Fourth, the prerogative of the President reduced. The method used is descriptive-qualitative method that is intended to describe an event in more detail.